Short-Time β-Alanine Supplementation on the Acute Strength Performance after High-Intensity Intermittent Exercise in Recreationally Trained Men - Marcelo Conrado Freitas; Jason Cholewa; Valéria Panissa; Giovanni Quizzini; João Vitor de Oliveira; Caique Figueiredo; Luis Alberto Gobbo; Erico Caperuto; Nelo Eidy Zanchi; Fabio Lira; Fabrício Eduardo Rossi (MDPI AG, 2019)
(1) Background: We investigated the effects of 28 days of beta-alanine (β-alanine) supplementation on the acute interference effect of high-intensity intermittent exercise (HIIE) on lower-body resistance exercise performance, body composition, and strength when combined with a resistance training program. (2) Methods: Twenty-two males were randomized into: β-alanine supplementation (6.4 g/day) or placebo (6.4 g/day maltodextrin) during 28 days. Total body water, intracellular and extracellular water, fat-free mass (FFM), and fat mass were assessed using bioelectrical impedance. Participants performed 5000-m HIIE (1:1 effort and rest ratio) followed by resistance exercise (four sets of 80% at 45° leg press until muscular failure) at baseline and after 28 days. The resistance training program consisted of three sets of 10 to 12 RM with 90 s of rest, four days per week. (3) Results: For the post-HIIE leg press volume, higher values were observed post-training than pre-training, but no group x time interaction was observed. There was a non-significant trend for an interaction in the FFM change (β-alanine = 2.8% versus placebo = 1.0%, p = 0.072). (4) Conclusion: Twenty-eight days of β-alanine supplementation did not prevent acute strength loss during resistance exercise after high-intensity interval exercise, nor increase strength or hypertrophic adaptations associated with resistance training.